An Integrative Theory Addressing Cyberharassment in the Light of Technology-Based Opportunism. Issue 4 (2nd October 2019) - Lowry, Paul Benjamin; Zhang, Jun; Moody, Gregory D.; Chatterjee, Sutirtha; Wang, Chuang; Wu, Tailai
Abstract: Scholars are increasingly calling for a deeper understanding of cyberharassment (CH) with the goal of devising policies, procedures, and technologies to mitigate it. Accordingly, we conducted CH research that (1) integrated social learning theory (SLT) and self-control theory (SCT); (2) empirically studied this model with two contrasting samples, experienced cyberharassers and less experienced cyberharassers; and (3) conducted post hoc tests to tease out the differences between the two samples. We show that for less experienced cyberharassers, CH is largely a social-psychological-technological phenomenon; whereas, for experienced cyberharassers, CH is primarily a psychological-technological phenomenon. Our study makes a threefold contribution: (1) it shows the value of integrating two theories in a holistic and parsimonious manner to explain CH; (2) it shows that SCT alone is a more relevant framework for experienced cyberharassers, whereas a combination of SCT and SLT better explains less experienced cyberharassers; and (3) it reveals that the role of technology in fostering CH is crucial, regardless of the sample. The differential, yet consistent, findings demonstrate that addressing CH is contingent upon not only identifying theoretical approaches but also identifying the particular samples to which these theoretical approaches will be more suitable. Of several implications for practice, the most important may be that anonymity, asynchronicity, and lack of monitoring are the technology choices that foster CH, and thus these should be mitigated in designing social media and other communication technologies